2021
DOI: 10.3390/jpm11030161
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Mesenchymal Stromal Cells in Neuroblastoma Therapy for Delivery of Anti-Cancer Agents and Hematopoietic Recovery

Abstract: Neuroblastoma is one of the most common pediatric cancers and a major cause of cancer-related death in infancy. Conventional therapies including high-dose chemotherapy, stem cell transplantation, and immunotherapy approach a limit in the treatment of high-risk neuroblastoma and prevention of relapse. In the last two decades, research unraveled a potential use of mesenchymal stromal cells in tumor therapy, as tumor-selective delivery vehicles for therapeutic compounds and oncolytic viruses and by means of suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 163 publications
0
4
0
Order By: Relevance
“…The result was in accordance with other studies that reported the highest level at 6–9 days ranging from 1500 to 8247 pg/ml and could constantly increase for 15 to 30 days after transduction [ 23 , 25 ]. Previous evidence has indicated that the modified MSCs could serve as an excellent local agent delivery vehicle for its innate homing ability [ 35 37 ]. The modified MSCs in conjunction with targeted drugs have been introduced in clinical practice: engineered UCMSCs produced TRAIL for intracranial glioma [ 38 ], and MSCs loaded with oncolytic reovirus ReoT3D for colorectal cancer [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The result was in accordance with other studies that reported the highest level at 6–9 days ranging from 1500 to 8247 pg/ml and could constantly increase for 15 to 30 days after transduction [ 23 , 25 ]. Previous evidence has indicated that the modified MSCs could serve as an excellent local agent delivery vehicle for its innate homing ability [ 35 37 ]. The modified MSCs in conjunction with targeted drugs have been introduced in clinical practice: engineered UCMSCs produced TRAIL for intracranial glioma [ 38 ], and MSCs loaded with oncolytic reovirus ReoT3D for colorectal cancer [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to clarify whether MSC favors BM infiltration by NB cells or NB cells alter the MSC differentiation process. Moreover, the use of mesenchymal cells as tumor-selective delivery vehicles for therapeutic compounds and oncolytic viruses needs to be reconsidered [ 84 ].…”
Section: Bm Cellular Composition In Nbmentioning
confidence: 99%
“…MSCs can migrate to tumor sites and inflamed sites as damaged tissues expressing ligands or specific receptors that stimulate the trafficking, recruitment, adhesion and extravasation of MSCs [ 138 ]. MSCs-derived exosomes play vital roles in cancer therapy resistance, including resistance to immunotherapy, chemotherapy, radiotherapy, and targeted therapy [ 69 , 139 , 140 ].…”
Section: Introductionmentioning
confidence: 99%